Teachers' Professional Competence in Increasing Students' Interest in Learning - Puspita, Radis; Lestari, Agus (Journal of Creativity Student, 2025)
This study focuses on the influence of teacher professional competence on students' learning interest at SMK Negeri 1 Kota Jambi. The background of this study is based on the reality in the field which shows variations in students' learning interest which can be influenced by teachers' ability to manage learning. This study aims to understand the extent to which teachers' mastery of the material, pedagogical skills, and the application of effective learning methods can increase students' learning interest. The research method used is descriptive qualitative with semi-structured interview techniques for teachers and students. The study's findings demonstrated that subject-matter experts can employ a wide range of effective teaching techniques. Furthermore, it has been demonstrated that fostering a favorable learning atmosphere in the classroom can boost students' motivation for learning. Children are more interested and motivated to learn when teachers employ innovative and dynamic teaching methods and establish deep emotional bonds with their students. These findings demonstrate how crucial it is to raise instructors' professional proficiency in order to provide engaging and productive learning environments for students.